Dietary soybean oil and choice white grease improve apparent ileal digestibility of amino acids in swine diets containing corn, soybean meal, and distillers dried grains with solubles - Kil, Dong Yong; Stein, Hans H (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary The objective of this experiment was to measure the effects of soybean oil (SBO) and choice white grease (CWG) on apparent ileal digestibility (AID) of amino acids (AA) in corn-soybean meal-distillers dried grains with solubles-based diets fed to growing pigs. Three diets were prepared. The control diet contained corn, soybean meal, distillers dried grains with solubles (DDGS), cornstarch, and no additional fat. Two additional diets were formulated by adding 5% SBO or 5% CWG to the control diet at the expense of cornstarch. Twelve growing barrows with initial body weight of 37.6 kg (standard deviation = 3.22) were equipped with a T-cannula at the end of the ileum and they were allotted to one of three dietary treatments during six experimental periods. The AID of indispensable AA (e.g., arginine, histidine, isoleucine, leucine,phenylalanine, and valine) and dispensable AA (e.g., alanine, aspartic acid, cysteine, and proline) was improved (p < 0.10) by the addition of 5% SBO or 5% CWG in the diets. The addition of SBO or CWG improved the AID of AA in a commercial-type diet containing corn, soybean meal, and distillers driedgrains with solubles, and the extent of improvement in the AID of AA was comparable between the two sources of dietary fat. Key words: amino acids, apparent ileal digestibility, choice white grease, soybean oil, swine. Resumen El objetivo de este experimento fue medir el efecto del aceite de soya (SBO) y la grasa blanca (grasa e cerdo, CWG) sobre la digestibilidad ileal aparente (DIA) de aminoácidos (AA) en dietas maíz-soya adicionadas con derivados solubles de destilería para cerdos en crecimiento. Tres dietas fueron preparadas. La dieta control contenía maíz, harina de soya, granos secos de destilería con solubles (DDGS), almidón de maíz, y sin grasa adicionada. Dos dietas adicionales fueron formuladas adicionando 5% de SBO o de GTC a la dieta control, a expensas de la fécula de maíz. Doce cerdos machos castrados, con peso inicial de 37.6 kg (desviación estándar =3.22), fueron equipados con una cánula en T en el extremo del íleo y fueron asignados a uno de los tres tratamientos dietarios durante seis periodos experimentales. La DIA de AA esenciales (por ejemplo, arginina, histidina, isoleucina, leucina, fenilalanina y valina) y no esenciales (por ejemplo, alanina, ácido aspártico, cisteína y prolina) se mejoró (p < 0.10) mediante la adición de 5% SBO o de 5% de CWG. La adición de SBO o CWG mejoró la DIA de AA en la dieta, y su nivel de mejoría fue similar entre las dos fuentes de grasa. Palabras clave: aceite de soya, aminoácidos, cerdos, digestibilidad ileal aparente, grasa blanca de cerdo. Resumo O objectivo deste experimento foi avaliar o efeito do óleo de soja (SBO) e gordura branca (de suino, CWG) sobre a digestibilidade ileal aparente (AID) de aminoácidos (AA) em dietas com adição de derivados de milho-soja solúvel de destilaria para suínos em crescimento. Três dietas foram preparadas. A dieta controle continha milho, farelo de soja, grãos secos de destilaria com solúveis (DDGS), amido de milho, e não tinha gordura adicionada. As outras duas dietas tinham uma adição de 5% SBO e a outra com 5% de GTC à custa de amido de milho. Doze suínos machos castrados, com peso inicial de 37.6 kg (DP = 3.22) foram equipados com uma cânula T no final do íleo. O núcleo do AA (por exemplo, arginina, histidina, isoleucina, leucina, fenilalanina e valina) e não-essenciais (por exemplo, alanina, ácido aspártico, cisteína e prolina) foi melhorada (p < 0.10) pela adição de 5% SBO CWG ou 5%. A adição de SBO ou CWG melhorou de AA na dieta e o nível de melhora foi semelhante entre as duas fontes de gordura. Palavras-chave: aminoácidos, digestibilidade ileal aparente, gordura branca de suíno, óleo de soja, suínos.